COGNITIVE BEHAVIORAL THERAPY FOR THE TREATMENT OF DEPRESSION: A CASE REPORT - AKTAŞ , Senem; KARAAZİZ , Meryem (SSD Journal, 2022)
Depression is the most common psychiatric case in the world and in our country. It presents itself as not being able to enjoy the things that one enjoyed before, decrease or increase in sleep, loss or increase in appetite, decrease in cognitive thinking level, indecision, and a state of constant sadness. Everyone is able to experience these symptoms at a certain time in their life or in their daily life. Depression can be seen in all periods, including young people, middle ages and advanced ages. However, in addition to these, the age range of 15-29 was determined as the most common age range. According to the researches, individuals with low socio-economic status have higher rates of depression compared to individuals with high socio-economic status, women compared to men and single people compared to married people. However, the person is diagnosed with depression depending on the duration, severity and diagnostic criteria of the depression. In order for a person to be diagnosed with depression, the symptoms must be observed for at least 2 weeks, at a level that disrupts the person’s daily life and activities. In this case report, cognitive behavioral therapy school was used to regulate the treatment process of our 24-year-old, single male patient who presented with symptoms of depression and to reduce the existing symptoms.